Spartina alterniflora Invasion Alters Carbon Exchange and Soil Organic Carbon in Eastern Salt Marsh of China. Issue 4 (28th July 2014) - Zhou, Lingyan; Yin, Shenglai; An, Shuqing; Yang, Wen; Deng, Qi; Xie, Dong; Ji, Haiting; Ouyang, Yan; Cheng, Xiaoli
<x xml:space="preserve">Abstract</x> We investigated carbon (C) fluxes from Spartina alterniflora community comparing with native C3‐plant (Suaeda salsa and Phragmites australis) communities as well as mudflat in a coastal marsh in eastern China by determining the net ecosystem exchange (NEE), ecosystem respiration (RECO) and soil respiration (RSOIL) monthly with static chambers over one year. Plant biological traits and soil organic carbon (SOC) were measured at the end of the growing season. Gross primary production (GPP) was calculated as the sum of RECO and NEE, while the respiration of aboveground plant (RAG) was assessed by the difference between RECO and RSOIL. The invasion of S. alterniflora significantly increased RECO, GPP, and RAG in salt marsh. The NEE in the S. alterniflora community was significantly lower than in mudflat and S. salsa community (p < 0.05), but was comparable to that in P. australis community (p > 0.05). RSOIL among sites with different communities did not show significant variations (p > 0.05). Surface water inhibited RSOIL and made it insensitive to changes in environmental factors across communities. Relative to other communities, the lower shoot–root ratio of S. alterniflora community together with its higher RECO and RAG determined a higher proportion of C allocated in belowground, which ultimately resulted in increment of SOC as well as increased GPP. The invasion of S. alterniflora potentially induces a negative feedback to the global climate change by regulating the C sequestration in salt marsh ecosystems.